1981
DOI: 10.1002/1097-0142(19810815)48:4<899::aid-cncr2820480406>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Cis-platinum in treatment of advanced or recurrent squamous cell carcinoma of the cervix: A phase ii study of the gynecologic oncology group

Abstract: Thirty-four patients with advanced or recurrent squamous cell carcinoma of the cervix no longer amenable to control with surgery and/or radiotherapy were treated with cis-platinum 50 mg/m2 intravenously every three weeks. Among 22 patients who had received no prior chemotherapy, three complete and eight partial responses were observed (response rate 50%), whereas only two partial responses were observed among 12 patients who had received prior chemotherapy (response rate 17%). The observed response rate was ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
101
0
6

Year Published

1984
1984
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(107 citation statements)
references
References 2 publications
0
101
0
6
Order By: Relevance
“…In patients with advanced or recurrent cervical cancer, most active single agents achieve overall response rates of 15 -35% (Thigpen et al, 1981;Bonomi et al, 1985;Takeuchi et al, 1991;McGuire et al, 1996;Verschraegen et al, 1997;Ivrin et al, 1998;Morris et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with advanced or recurrent cervical cancer, most active single agents achieve overall response rates of 15 -35% (Thigpen et al, 1981;Bonomi et al, 1985;Takeuchi et al, 1991;McGuire et al, 1996;Verschraegen et al, 1997;Ivrin et al, 1998;Morris et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…For patients with stage IV disease or with recurrence after radiotherapy, however, the prognosis is still dismal (Thigpen et al, 1995). In such patients, most of the active chemotherapy agents achieve overall response rates of 20 -35% when given as monotherapy, with a median response duration of 3 -6 months and a survival time of 5 -9 months (Thigpen et al, 1981;McGuire et al, 1996). Many combination chemotherapy regimens have also been explored during the last two decades.…”
mentioning
confidence: 99%
“…As for the rationale of associating adjuvant chemotherapy, most authors consider that it should be taken in consideration because the splenic lesion is in fact a distant metastasis necessitating systemic therapy (26,27). However, the presence of an isolated distant metastasis is considered by some authors as a sign of a less aggressive biological subtype of the tumor as compared to those cases that present disseminated lesions, thus transforming the patient into the perfect candidate for surgery (28,29).…”
Section: Case Reportmentioning
confidence: 99%
“…3,4 Since the publication of the initial studies examining cisplatin in the treatment of cervical cancer, a number of effective single-agent and combination drug regimens have been identified that exhibited improved response rates, without a significant effect on overall survival. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] The poor oncologic outcome in this patient population represents an unmet clinical need and has driven the exploration of new treatment paradigms. 3 Most recently, the results of Gynecologic Oncology Group (GOG) protocol 240 were presented and Scan the QR Code with your phone to obtain FREE ACCESS to the articles featured in the Clinical Therapeutics topical updates or text GS2C65 to 64842.…”
Section: Introductionmentioning
confidence: 99%